Fault detection in discrete dynamic systems with uncertainty based on interval optimization - Li, Wei; Tian, Xiaoli (Mathematical Modelling and Analysis, 2011)
The imprecision and the uncertainty of many systems can be expressed with interval models. This paper presents a method for fault detection in uncertain discrete dynamic systems. First, the discrete dynamic system with uncertain parameters is formulated as an interval optimization model. In this model, we also assume that there are some errors of observation values of the inputs/outputs. Then, M. Hladík’s newly proposed algorithm is exploited for this model. Some numerical examples are also included to illustrate the method efficiency.